Application of Videoscribe Media to Cognitive Learning Outcomes in Social Science Learning at Madrasah Ibtidaiyah: Penerapan Media Videoscribe Terhadap Hasil Belajar Kognitif pada Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Ibtidaiyah - Dewi, Nur Alfina; Afandi, Rifki (Indonesian Journal of Education Methods Development, 2023)
The purpose study are (1) to find out whether there was an effect of videoscribe learning media on social studies learning outcomes for grade 4 at MI Nurus syafi'I, (2) to find out how much influence videoscribe learning media had on social studies learning outcomes for grade 4 at MI Nurus syafi'i This study uses a quantitative experimental research design using the PreExperimental – One Group Pretest Posttest Design research design. The results showed that there was a positive and significant influence on the videoscribe learning media on the social studies learning outcomes of fourth grade students of MI Nurusyafi'I Gedangan, as evidenced by the t-count value of 10,947> 2,074, and the magnitude of the effect can be seen from Cohen's d calculations which show the result of 2.12 > 0 ,8 The conclusion of this study is that there are a major influence on student cognitive learning outcomes at MI Nurus Syafii.